Bulgaria : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2004)
This paper examines Bulgaria's 2004 Article IV Consultation and Ex Post Assessment of Longer-Term Program Engagement. Foreign direct investment inflows have been strong, reserves are rising, and competitiveness appears broadly adequate. Fiscal policy has been tightened in 2003, as the government saved half of the revenue overperformance and reduced the deficit to 0.4 percent of GDP. The pace of structural reform has slowed, with two large privatizations and fiscal structural measures delayed.